1986
DOI: 10.1111/j.1365-2818.1986.tb02721.x
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature light microscopy and its application to study freezing in aqueous solutions and biological cell suspensions

Abstract: SUMMARY The freezing of biological cell suspensions can be understood in terms of ice formation in the external suspension medium and the cellular reactions to the changing environment. Cryomicroscopy allows a quantitative analysis of both categories of phenomena. Besides freezing stages of appropriate thermal design, the components used for that purpose include a microcomputer (PSI 80) based control system, an image analysis system (Intellect 100) and a spectrophotometer (MPV compact). The investigation of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The solutions were first degassed, and the gas content was then adjusted prior to the experiment. Nucleation, growth and encapsulation were observed and evaluated dynamically by means of a cryomicroscope in combination with a video-recording system and digital image processing (Korber et al 1984(Korber et al , 1986. Two types of freezing stages were used, one of them yielding a constant and…”
Section: Experimental Results and Observationsmentioning
confidence: 99%
“…The solutions were first degassed, and the gas content was then adjusted prior to the experiment. Nucleation, growth and encapsulation were observed and evaluated dynamically by means of a cryomicroscope in combination with a video-recording system and digital image processing (Korber et al 1984(Korber et al , 1986. Two types of freezing stages were used, one of them yielding a constant and…”
Section: Experimental Results and Observationsmentioning
confidence: 99%
“…As both experimental techniques, light cryomicroscopy (Scheiwe & Korber, 1982cKorber et al, 1986;Korber, 1988;Englich, 1988) and low-temperature DSC Jochem & Korber, 1987;Englich, 1988), have been described previously in detail, only a short outline is given here with mention of the most important steps and parameters.…”
Section: Materials a N D M E T H O D Smentioning
confidence: 99%
“…Carte,8 as well as Bari and Hallett,9 discussed the formation air bubbles in ice, hoping that the study can help explain the formation of hailstone. Kõrber et al 10 found that air bubbles were formed in cooling cell suspensions. This is harmful in the preservation of cells and tissues, since the existence of air bubbles may cause different stress distributions in the ice and lead to the braking of ice, which may kill the preserved cells.…”
Section: Resultsmentioning
confidence: 99%